1992
DOI: 10.1073/pnas.89.2.584
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the alpha 1 subunit of a voltage-dependent calcium channel expressed in pancreatic beta cells.

Abstract: The isoforms of the a, subunits of voltagedependent Ca2+ channels expressed in human pancreatic islets were identified by using a pair of degenerate oligonucleotide primers and the polymerase chain reaction (PCR) to amplify mRNAs encoding a, subunit-like sequences. The sequences of the PCR products indicate that islets express the heart-type a, subunit as well as a second isoform whose complete sequence has not been previously reported. The sequences of cloned cDNAs encoding the human fl-cell, or neuroendocrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(108 citation statements)
references
References 37 publications
(39 reference statements)
3
105
0
Order By: Relevance
“…cDNA of the third gene (CaCh3) was isolated from neural and endocrine tissues and represents a neuroendocrinespecific L-type calcium channel (Williams et al 1992a, Seino et al 1992, whereas the gene products of the fourth and fifth genes (CaCh4 and CaCh5) have been found exclusively in neural tissues. Calcium channels transiently expressed from cRNA of CaCh4 induce high-voltage-activated calcium currents that are insensitive to nifedipine and o-conotoxin but are inhibited by a mixture of toxins from the funnel web spider that characterize this channel as a P-type calcium channel (Mori et al 1991).…”
Section: The a Subunitmentioning
confidence: 99%
“…cDNA of the third gene (CaCh3) was isolated from neural and endocrine tissues and represents a neuroendocrinespecific L-type calcium channel (Williams et al 1992a, Seino et al 1992, whereas the gene products of the fourth and fifth genes (CaCh4 and CaCh5) have been found exclusively in neural tissues. Calcium channels transiently expressed from cRNA of CaCh4 induce high-voltage-activated calcium currents that are insensitive to nifedipine and o-conotoxin but are inhibited by a mixture of toxins from the funnel web spider that characterize this channel as a P-type calcium channel (Mori et al 1991).…”
Section: The a Subunitmentioning
confidence: 99%
“…In contrast to other Ca 2ϩ channels, wherein the heterologous expression of the pore-forming ␣ subunit closely mirrors the native channel current, the biophysical properties of the expressed Ca V 1.3 are quite distinct from typical hair cell Ca 2ϩ currents (Bell et al 2001;Koschak et al 2001;Mikami et al 1989;Seino et al 1992;Williams et al 1992;Xu and Lipscombe 2001). Although it has been suggested that splice variants of Ca V 1.3␣ 1 channel in the chick basilar papilla may suffice to confer the unique properties of the DHP-sensitive Ca 2ϩ currents in hair cells (Kollmar et al 1997b), in other systems, there is ample evidence to suggest that co-assembly of auxiliary ␤ and ␣ 2 ␦ subunits with the ␣ 1 subunit may contribute to the properties of the native Ca 2ϩ current.…”
Section: Introductionmentioning
confidence: 99%
“…Transcripts encoding L-type Ca 2+ channels (Fig. 2) thought to be largely responsible for Ca 2+ influx in beta cells were identified in the early 1990's [30,31,32], however there is still some controversy regarding the role of other Ca 2+ channels as N-type, P/Q-type and T-type channels have also been detected in insulin-secreting cells [33]. Clinically, some cases of PHHI, particularly those resulting from K ATP channel defects which are therefore not responsive to diazoxide, could be treated with VDCC antagonists [34,35,36].…”
mentioning
confidence: 99%